THEORETICAL BASIS OF EFFECTIVE MECHANISMS OF LOCAL BUDGET EXPENDITURE PLANNING - Ruzmetov Javlon Islamboevich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This paper explores the theoretical foundations and modern approaches to planning local budget expenditures effectively. Emphasizing both conceptual frameworks and empirical evidence, the paper examines fiscal decentralization, performance-based budgeting, and citizen participation as key pillars of planning efficiency. Through a review of international experiences and comparative case studies, the paper identifies critical mechanisms and tools for improving the strategic allocation of public resources at the subnational level. The conclusion offers policy recommendations relevant for countries undergoing decentralization reforms.